2019
DOI: 10.1038/s41467-019-12906-y
|View full text |Cite
|
Sign up to set email alerts
|

An anionic, endosome-escaping polymer to potentiate intracellular delivery of cationic peptides, biomacromolecules, and nanoparticles

Abstract: Peptides and biologics provide unique opportunities to modulate intracellular targets not druggable by conventional small molecules. Most peptides and biologics are fused with cationic uptake moieties or formulated into nanoparticles to facilitate delivery, but these systems typically lack potency due to low uptake and/or entrapment and degradation in endolysosomal compartments. Because most delivery reagents comprise cationic lipids or polymers, there is a lack of reagents specifically optimized to deliver ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…The endosomolytic polymer is formed by the PEG block that contributes to colloidal stability of the nanoparticles, and by the two D ((dimethylamino)ethyl methacrylate) and B (butyl methacrylate) monomers, which are implied in the pH-responsive function. Since it has been assumed that the efficiency of endosome escape is higher in early endosomal vesicles (pH = 6.8) [ 194 ], various PEG-DB compositions (specifically increasing the percentage of hydrophobic B content from 20% to 70%) have been screened at different pH values in order to evaluate whether a robust membrane disruption at pH 6.8 correlates with the intracellular PNA bioactivity. In this study, they first observed that the stability of the polymer coating increases with the hydrophobicity (% B), which also drives the lipid bilayer membrane insertion.…”
Section: Inorganic Nanocarriersmentioning
confidence: 99%
“…The endosomolytic polymer is formed by the PEG block that contributes to colloidal stability of the nanoparticles, and by the two D ((dimethylamino)ethyl methacrylate) and B (butyl methacrylate) monomers, which are implied in the pH-responsive function. Since it has been assumed that the efficiency of endosome escape is higher in early endosomal vesicles (pH = 6.8) [ 194 ], various PEG-DB compositions (specifically increasing the percentage of hydrophobic B content from 20% to 70%) have been screened at different pH values in order to evaluate whether a robust membrane disruption at pH 6.8 correlates with the intracellular PNA bioactivity. In this study, they first observed that the stability of the polymer coating increases with the hydrophobicity (% B), which also drives the lipid bilayer membrane insertion.…”
Section: Inorganic Nanocarriersmentioning
confidence: 99%
“…In addition to optimizing nuclear acids condensation and the surface potential of nanoparticles for enhanced uptake, it is also possible to increase the negative charge of the cell membrane through pretreatment to increase cellular uptake. Duvall's group designed an anionic polymer poly(propylacrylic acid) (PPAA) 47 . Pretreatment of cells with PPAA can enhance cell uptake and endosome escape of cationic biomacromolecules and nanostructures (Figure 4).…”
Section: Polymeric Gene Delivery Enhancersmentioning
confidence: 99%
“…Schematic diagram of the mechanism of the anionic polymer PPAA‐mediated cationic peptide uptake and intracellular delivery. Reproduced with permission 47 . Copyright 2019, the Authors…”
Section: Polymeric Gene Delivery Enhancersmentioning
confidence: 99%
“…The time plotted indicated the first application for pH-dependent membrane permeabilization, instead of the first reported synthesis of the polymer. (Wang, 2018;Evans et al, 2019). Albeit less renowned, recent studies show their emerging potentials for proteins, genes, and vaccine delivery (Mukalel et al, 2018;Qiu et al, 2018;Evans et al, 2019;Jacobson et al, 2019;Kopytynski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%